Metabolic cost of osmoregulation by the gastro-intestinal tract in marine teleost fish - Little, A.; Pasparakis, C.; Stieglitz, J.; Grosell, M. (Frontiers in Physiology, 2023)
Although dozens of studies have attempted to determine the metabolic cost of osmoregulation, mainly by comparing standard metabolic rates (SMR) in fish acclimated to different salinities, consensus is still lacking. In the present study, using the Gulf toadfish, Opsanus beta, we aimed to determine the metabolic cost of esophageal and intestinal osmoregulatory processes by estimating ATP consumption from known ion transport rates and pathways and comparing these estimates with measurements on isolated tissues. Further, we performed whole animal respirometry on fish acclimated to 9, 34 and 60 ppt. Our theoretical estimates of esophageal and intestinal osmoregulatory costs were in close agreement with direct measurements on isolated tissues and suggest that osmoregulation by these tissues amounts to ~2.5% of SMR. This value agrees well with an earlier attempt to estimate osmoregulation cost from ion transport rates and combined with published measurements of gill osmoregulatory costs suggests that whole animal costs of osmoregulation in marine teleosts is ~7.5% of SMR. As in many previous studies, our whole animal measurements were variable between fish and did not seem suited to determine osmoregulatory costs. While the esophagus showed constant metabolic rate regardless of acclimation salinity, the intestine of fish acclimated to higher salinities showed elevated metabolic rates. The esophagus and the intestine had 2.1 and 3.2-fold higher metabolic rates than corresponding whole animal mass specific rates, respectively. The intestinal tissue displays at least four different Cl- uptake pathways of which the Na+:Cl-:2K+ (NKCC) pathway accounts for 95% of the Cl- uptake and is the most energy efficient. The remaining pathways are via apical anion exchange and seem to primarily serve luminal alkalinization and the formation of intestinal CaCO3 which is essential for water absorption.